Perianal abscess in children. - Abercrombie, J. F. (Royal College of Surgeons of England, 1992)
The records of 16 children presenting with a diagnosis of perianal abscess, over a 5-year period, were reviewed. The clinical and microbiological features of paediatric perianal abscesses are similar to those found in adults, although the incidence of associated diseases is higher in paediatric patients. Perianal abscesses in children are best treated by incision and drainage. The presence of an underlying contributing disease should be excluded.